Ideological and Political Education in All Disciplines as a Pedagogical Problem in Higher Education in China - Yao W. (Interactive science, 2020)
ideological and political studies in higher education in China are present in all disciplines, many universities have included relevant requirements in the curriculum. Universities in China have actively pursued research projects and pedagogical tests and gained significant experience. Despite the fact that this idea is already five years old, some factors that impede its effective practical application are still present. This article discusses these factors and analyzes their share in education.
Keywords: высшее образование; Китай; дисциплина; higher education; China; Discipline; ideological and political education; идейно-политическое обучение